Educação escolar no ambiente prisional: sob o olhar das experiências dos sujeitos - Brancalione, Jéssica Mara (2020)
This research aims to study prison education in a maximum security prison unit in the interior of Santa Catarina - the Chapecó Industrial Penitentiary. The serious situation of national prisons has been raising fervent debates about what measures should be taken to face violence in these environments. Education is an appropriate and promising path for those who believe in the detainee's re-socialization. However, it is known that prison education does not find in the concrete reality of our prison units an educational space suitable for the re-socializing human formation. In this perspective, the present dissertation presents the following question as a research problem: What are the experiences of detainees, prison staff and teachers in relation to school education in the Industrial Penitentiary of Chapecó-SC? This is a bibliographic, documentary and field research in which Narrative Interviews and Logbook were conducted, in which we sought to analyze the experiences of correctional officers, teachers and students / inmates about the prison environment and formal education. It was concluded that the research subjects understand education as a way to work, without, however, considering the critical role that education can have, demonstrating the obedience, traditionally understood as passivity, which is analyzed by Foucault in its positivity, in the sense that the body is constrained, subjected and subjected by forces that aim to take its useful effects out of it, that aim to make it, itself, productive. However, in a sigh of hope, it is still believed that the emancipatory role of education is minimized in its capacity, and that school education can indeed be a great ally in search of the dreamed 'resocialization'.